Diagnostic markers of severe diabetic macular edema in patients with type 2 diabetes - S.A. Suk; S.Yu. Mogilevskyy (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Diabetic macular edema (DME) is one of the common causes of vision loss in patients with type 2 diabetes mellitus (DM). In the pathogenesis of DME, the main role is played by the breakdown of the blood-retinal barrier as a result of an increase in vascular endothelial growth factor and the expression of pro-inflammatory cytokines. This breakdown leads to hyperpermeability of the vessels with subsequent formation of DME. With the emergence of the optical coherence tomography (OCT), the possibilities of studying markers for early detection and prediction of DME are expanding, which is an urgent task of modern ophthalmology. The purpose of the study was to investigate diagnostic markers of severe diabetic macular edema in patients with type 2 diabetes. Materials and methods. Six hundred and eighty patients (1296 eyes) of the Ukrainian population with nonproliferative diabetic retinopathy and type 2 DM were under observation. The nature and frequency of DME development were studied in them. Two hundred and three patients (360 eyes) with DME were not treated due to refusal. Eyes with severe diabetic macular edema (DMN3) were selected from this group, and these patients was the target of our study. Ophthalmic examination methods included: history taking, visometry, refractometry, posterior ocular biomicroscopy, pneumotonometry, fundus photography, OCT, OCT angiography, microperimetry. Statistical data processing was carried out. The observation period was 3 months. Results. During referral of the patients, DME3 was detected in 50 eyes (13.89 %). The average uncorrected visual acuity (UCVA) was 0.15 ± 0.01. Maximum corrected visual acuity (MCVA) averaged 0.32 ± 0.01. According to OCT, area thickness was 355.68 ± 1.80 μm, min in fovea — 358.54 ± 2.40 μm, central sector — 401.06 ± 2.09 μm, volume — 10.42 ± 0.10 mm3, nerve fiber layer (NFL) + ganglion cell layer (GCL) + inner plexiform layer (IPL) average — 138.3 ± 0.7 μm, NFL + GCL + IPL min — 122.78 ± 0.60 μm, GCL — 97.2 ± 1.0 μm, NFL — 42.12 ± 0.20 μm. According to OCT angiography, the surface area of the superficial foveal avascular zone (FAZ) was on average 0.780 ± 0.002 mm2, the surface area of the deep FAZ was 0.720 ± 0.002 mm2. The average density of the vascular pattern of the superficial plexus was 45.68 ± 0.20 %, deep plexus — 46.46 ± 0.20 %. After 3 months, DME3 was recorded in 50 eyes (13.89 %) in patients with nonproliferative diabetic retinopathy and type 2 DM. UCVA in them averaged 0.14 ± 0.01, MCVA averaged 0.32 ± 0.01. According to OCT data, area thickness was 357.62 ± 1.80 μm, min in fovea — 360.04 ± 2.40 μm, central sector — 403.52 ± 2.10 μm, volume — 10.67 ± 0.10 mm3, NFL + GCL + IPL average — 139.26 ± 0.40 μm, NFL + GCL + IPL min — 124.38 ± 0.30 μm, GCL — 98.94 ± 0.30 μm, NFL — 42.42 ± 0.20 μm. According to the OCT angiography, superficial FAZ was 0.780 ± 0.002 mm2, deep FAZ was 0.720 ± 0.002 mm2, the average density of the vascular pattern of the superficial plexus was 45.17 ± 0.20 %, the average density of the vascular pattern of the deep plexus was 46.22 ± 0.20 %. Conclusions. In patients of the Ukrainian population with type 2 DM, the average frequency of DME 3 was 13.89 %. There was a reliable relationship between UСVA and MCVA in DME 3 in patients with type 2 diabetes and OCT indicators, namely area thickness, min in fovea, central sector, NFL + GCL + IPL average, NFL + GCL + IPL min, GCL and NFL (p < 0.01). A significant relationship was found between UСVA and MCVA in DME 3 in patients with type 2 diabetes and the state of microcirculation of macular zone according to the OCT angiography indicators such as superficial FAZ, deep FAZ, average density of the vascular pattern of the superficial and deep plexus (p < 0.01).